2020
DOI: 10.1101/2020.02.27.967703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling Crucivirus Diversity by Mining Metagenomic Data

Abstract: The discovery of cruciviruses revealed the most explicit example of a common protein homologue between DNA and RNA viruses to date. Cruciviruses are a novel group of circular Rep-encoding ssDNA (CRESS-DNA) viruses that encode capsid proteins (CPs) that are most closely related to those encoded by RNA viruses in the family Tombusviridae. The apparent chimeric nature of the two core proteins encoded by crucivirus genomes suggests horizontal gene transfer of CP genes between DNA and RNA viruses. Here, we identifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…This indicates that the dinoRNAV mcp sequences reported here constitute exogenous viral infections, rather than endogenous viral elements (EVEs; [62]) within their host's genome. Considering that the gene amplicons reported here were generated from unfractionated coral tissue, dinoRNAV mcp detections in this study could potentially arise from four sources: RNA genomes within intact dinoRNAV capsids (sensu [29]); mcp genes that are being expressed in host cells during a dinoRNAV replication cycle; free dinoRNAV genomes that may occur as extrachromosomal RNA in a latent [26] or carrier state similar to pseudolysogeny [82,83]; and /or chimeric RNA viruses with analogous mcp gene sequences [61]. However, the identification of highly abundant transcripts with homology to Symbiodiniaceae-associated dinoRNAV RdRp genes in the metatranscriptomes (Table S2, S3) indicates that mcp gene amplicons in this study are most parsimoniously interpreted as derived from dinoRNAVs [79,80].…”
Section: Healthy Corals Contain Millions Of Symbiodiniaceae Cells Per CM 2 Of Coral Tissue; Our Resultsmentioning
confidence: 99%
“…This indicates that the dinoRNAV mcp sequences reported here constitute exogenous viral infections, rather than endogenous viral elements (EVEs; [62]) within their host's genome. Considering that the gene amplicons reported here were generated from unfractionated coral tissue, dinoRNAV mcp detections in this study could potentially arise from four sources: RNA genomes within intact dinoRNAV capsids (sensu [29]); mcp genes that are being expressed in host cells during a dinoRNAV replication cycle; free dinoRNAV genomes that may occur as extrachromosomal RNA in a latent [26] or carrier state similar to pseudolysogeny [82,83]; and /or chimeric RNA viruses with analogous mcp gene sequences [61]. However, the identification of highly abundant transcripts with homology to Symbiodiniaceae-associated dinoRNAV RdRp genes in the metatranscriptomes (Table S2, S3) indicates that mcp gene amplicons in this study are most parsimoniously interpreted as derived from dinoRNAVs [79,80].…”
Section: Healthy Corals Contain Millions Of Symbiodiniaceae Cells Per CM 2 Of Coral Tissue; Our Resultsmentioning
confidence: 99%
“…In general, for viruses in the phylum Cressdnaviricota , the CPs are more diverse than the Reps. Furthermore, the CPs of geminiviruses share homology to those of albetoviruses (linear ssRNA(+) genomes) [ 65 ], and a group of unclassified cressdnavirues have CPs that are homologous to those of tombusviruses (linear ssRNA(+) genomes) [ 64 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Reps identified in this study are highlighted in green and relevant clades of the tree are shown in the expanded view. Sequences with taxa names CruV-203, -227, -319, and -320 are from metagenomic derived sequences reported in de la Higuera et al [ 64 ] and do not have accession #s assigned. The level of branch support (>0.8) is depicted as different sized shaded circles.…”
Section: Figurementioning
confidence: 99%
“…Evolutionary analysis of microphage genomes assembled from public virome sequences indicates that coinfection events may have primed genetic exchange between ssDNA or dsDNA viruses (146). Metagenomic studies that uncovered chimeric RNA-DNA hybrid viruses imply that systematic coinfections have played crucial roles in the ecology and evolution of these viruses (147,148). For example, evaluation of 13,103 viruses from 6,564 microbial hosts in three distinct large-scale microbial data sets predicted that host ecology and VVIs strongly regulate frequency and extent of viral coinfections (149) (Figure 4).…”
Section: Spontaneousmentioning
confidence: 99%